2020
DOI: 10.1177/0972150920920440
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Unemployment and Governance on Poverty in Pakistan: A Fresh Insight from Non-linear ARDL Co-integration Approach

Abstract: This article aims to give a fresh insight into the non-linear relationship between unemployment, governance, and poverty in Pakistan. For the purpose, the study utilizes data from 1984 to 2016 by employing a nonlinear ARDL co-integration approach. The findings provide an insight that poverty responds asymmetrically due to positive or negative shocks in unemployment and governance. Moreover, the results suggest that applying linear models on poverty modelling may mislead the inference. The findings of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 62 publications
1
17
0
5
Order By: Relevance
“…This weightage also declined up to a level at which the explanatory power of private investment for the forecast error in the unemployment rate can reach 1.34% in the 9 th period. Meo et al (2020) gave a fresh idea about the non-linear relationship between unemployment, governance, and poverty in Pakistan. The data were taken from 1984-2016 by applying the non-linear ARDL co-integration test.…”
Section: Introductionmentioning
confidence: 99%
“…This weightage also declined up to a level at which the explanatory power of private investment for the forecast error in the unemployment rate can reach 1.34% in the 9 th period. Meo et al (2020) gave a fresh idea about the non-linear relationship between unemployment, governance, and poverty in Pakistan. The data were taken from 1984-2016 by applying the non-linear ARDL co-integration test.…”
Section: Introductionmentioning
confidence: 99%
“…The findings related to disaggregated price levels on both absolute and relative poverty were found mixed. Afterward, Meo et al [12] used the NARDL approach on a sample from 1984 to 2016 for Pakistan and found asymmetric relation between poverty and its determinants like unemployment and governance. The study further disclosed that the positive changes in unemployment and governance had more significant impacts on poverty than negative changes in unemployment and governance.…”
Section: The Impact Of Macroeconomic Factors On Povertymentioning
confidence: 99%
“…The training program is also based on industry needs to equip graduates (Hofmann et al, 2021;Nopiah et al, 2018). Training participants are expected to have competence after attending the training so that they are able to compete and enter the world of work (García-Castilla et al, 2019;Meo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%